Noun and verb knowledge in monolingual preschool children across 17 languages: Data from Cross-linguistic Lexical Tasks (LITMUS-CLT) - Haman, Ewa; Luniewska, Magdalena; Hansen, Pernille; Simonsen, Hanne Gram; Chiat, Shula; Bjekic, Jovana; Blaziene, Agne; Chyl, Katarzyna; Dabasinskiene, Ineta; de Abreu, Pascale Engel; Gagarina, Natalia; Gavarro, Anna; et al. (Taylor & Francis Inc., 2017)
This article investigates the cross-linguistic comparability of the newly developed lexical assessment tool Cross-linguistic Lexical Tasks (LITMUS-CLT). LITMUS-CLT is a part the Language Impairment Testing in Multilingual Settings (LITMUS) battery (Armon-Lotem, de Jong & Meir, 2015). Here we analyse results on receptive and expressive word knowledge tasks for nouns and verbs across 17 languages from eight different language families: Baltic (Lithuanian), Bantu (isiXhosa), Finnic (Finnish), Germanic (Afrikaans, British English, South African English, German, Luxembourgish, Norwegian, Swedish), Romance (Catalan, Italian), Semitic (Hebrew), Slavic (Polish, Serbian, Slovak) and Turkic (Turkish). The participants were 639 monolingual children aged 3;0-6;11 living in 15 different countries. Differences in vocabulary size were small between 16 of the languages; but isiXhosa-speaking children knew significantly fewer words than speakers of the other languages. There was a robust effect of word class: accuracy was higher for nouns than verbs. Furthermore, comprehension was more advanced than production. Results are discussed in the context of cross-linguistic comparisons of lexical development in monolingual and bilingual populations.
13th International Congress for the Study of Child Language -- JUL, 2014 -- Amsterdam, NETHERLANDS
WOS: 000415973600002
PubMed ID: 28441085
Keywords: Lexical Development; Cross-Linguistic Comparison; Basic Word Classes; Word Comprehension; Word Production